Análisis Y Efectos En El Comercio De La Ciudad De Babahoyo Con La Elaboración De Las Facturas Electrónicas Dispuesto Por El Servicio De Rentas Internas... - Solano Naranjo, Hilda Johanna (2014)
The results allowed us to reach the following conclusion: The tax administration has a modern and appropriate regulatory and technological development to its economic system that allows the use of electronic invoicing and other electronic tax documents, such as buying and selling books , notes payables and / or credits , Outrun among others , while in Ecuador so far this service has not been developed , counting only with legislative initiatives such as the Law on Electronic Signatures and Message , which gives the probative value of the documents issued electronically, the Special Law against Cybercrime which aims to protect systems that use information technology as well as prevent crimes committed against such systems and their components, and the General Rules of the VAT Act added that provides the ability to create special billing arrangements for e-commerce transactions ...